The PENGARUH PENGGUNAAN MEDIA FLANACARAKA TERHADAP KETERAMPILAN MENULIS SANDHANGAN SWARA PADA SISWA KELAS IV SDN TAMPINGMOJO JOMBANG - misna andriani yani (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Abstract: This study aims to know the differences students writing ability on Sandhangan Swara between control and experimental class by using Flanacaraka Media at IV Class Students SDN Tampingmojo Jombang. This research is Quasy Experimental design type Nonequivalent Control Group Class approach. The population in this research consist of 41 students at IV Class in SDN Tampingmojo. The researcher divides the class as control and experimental class. Experimental class consist of 21 students were taught by using Flanacaraka Media and control class consist of 20 students were not. The result of the use flanacaraka media toward students writing ability on sandhangan swara at IV class students SDN Tampingmojo. The statistical test using the t test, namely tcount (2,45) > ttable (2,02), at a significant 0,05 level which means that Ho is rejected and Ha is accepted. Furthermore, the students’ behavior shown more active, conducive, and more enthusiasm on teaching learning process. Therefore, flanacaraka media very effective toward students writing ability on sandhangan swara in elementary school.